KECURANGAN LAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR (Jurnal Riset Akuntansi, 2022)
Fraudulent financial statement has a bad impact on users of financial statements, especially for investors who provide funds to companies. Investors need to be observant in analyzing the company's financial statements. Therefore, it is necessary to know several factors that influence companies to commit fraudulent financial statements. This study aims to examine the effect of external pressure, financial targets and the ineffective monitoring on fraudulent financial statement at manufacturing companies listed on the Indonesia Stock Exchange. This research is a quantitative research. The sampling technique in this study used a purposive sampling method based on the criteria given. Accordingly, there were 35 companies as samples in 3 consecutive years. The data analysis technique in this study used logistic regression analysis with the help of the IMB SPSS application. The results of the study found that: (1) external pressure had a significant negative effect on fraudulent financial statement, (2) financial targets had a significant negative effect on fraudulent financial statement, and (3) ineffective monitoring had no effect on fraudulent financial statement. This research can contribute to the Public Accounting Firm and investors and potential investors to pay attention to the leverage ratio and ROA in external pressure variables and financial targets in a company's financial statements. Keywords: Fraudulent Financial Statement, External Pressure, Financial Targets, Ineffective Monitoring.